Mobility of Iron-Cyanide Complexes in a Humic Topsoil under Varying Redox Conditions - Thilo Rennert; Tim Mansfeldt (Applied and Environmental Soil Science)
The potentially toxic Fe-CN complexes ferricyanide, [FeIII(CN)6]3−, and ferrocyanide, [FeII(CN)6]4−, undergo a variety of redox processes in soil, which affect their mobility. We carried out microcosm experiments with suspensions of a humic topsoil (pH 5.3; Corg 107 g kg-1) to which we added ferricyanide (20 mg l-1). We varied the redox potential (EH) from −280 to 580 mV by using O2, N2 and glucose. The decrease of EH led to decreasing concentrations of Fe-CN complexes and partial reductive dissolution of (hydrous) Fe and Mn oxides. The dynamics of aqueous Fe-CN concentrations was characterized by decreasing concentrations when the pH rose and the EH dropped. We attribute these dependencies to adsorption on organic surfaces, for which such a pH/EH behavior has been shown previously. Adsorption was reversible, because when the pH and EH changed into the opposite direction, desorption occurred. This study demonstrates the possible impact of soil organic matter on the fate of Fe-CN complexes in soil.